2014
DOI: 10.3233/nre-131024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceptive rehabilitation on balance control in patients with Parkinson's disease

Abstract: BACKGROUND: Subjects affected by Parkinson's disease have substantially impaired static and dynamic balance, leading to diminished functional ability. Conventional and innovative exercises have been suggested, but most of them were focused on motor features of posture and gait, deserving poor attention to perceptive aspects of balance. OBJECTIVE: To evaluate the efficacy of the perceptive rehabilitation, based on perceptual surfaces, for postural balance (primary aim) and pain, depression and activity daily li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Also, the maintenance of chronic low back pain is linked to a disorder of altered perception of the trunk 23 ) . Perceptual Surfaces (PSs) reduce static and dynamic balance impairments, even in patients with Parkinson disease (PD) 24 ) . The function of the trunk is crucial in PD: other studies have shown how vibrotactile biofeedback of the trunk improves postural stability in PD 25 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the maintenance of chronic low back pain is linked to a disorder of altered perception of the trunk 23 ) . Perceptual Surfaces (PSs) reduce static and dynamic balance impairments, even in patients with Parkinson disease (PD) 24 ) . The function of the trunk is crucial in PD: other studies have shown how vibrotactile biofeedback of the trunk improves postural stability in PD 25 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation to correct abnormal posture demonstrated inverse (left‐sided) correlation. Paolucci et al also reported the efficacy of perceptive training for treating balance impairment in PD patients.…”
Section: Discussionmentioning
confidence: 96%
“…(A) Perceptive Rehabilitation Program . Perceptive surface group (PS-group) received a treatment that, as described by Morone and colleagues [ 36 38 ], is a therapeutic approach based on the interaction between the patient's back or painful area and a support surface, composed of small latex cones with various dimensions (height: 3–8 cm; base diameter: 2–4 cm) and elasticities. The inferior bases of these cones are applied to a rigid wood surface using elastic strips; normally, over 100 cones are used for each session ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“… In subsequent sessions, cones with varying elasticities were positioned by the therapist to improve the symmetry of contact between the surface and the patient's back, taking into consideration the hyperemia in the previous session. The objective of this step was to obtain reafferent information from the trunk and body, the positions of which were altered in FM, using elements of motor imagery [ 38 41 ]. Each phase of the session ended with 10 minutes of global stretching of the upper limbs and lower limbs.…”
Section: Methodsmentioning
confidence: 99%